The circular archetype in microcosm : the carved stone balls of late Neolithic Scotland - Stewart-Moffitt, Chris L., (Archaeopress Archaeology, 2022)
This study is the culmination of seven years research into the Carved Stone Balls of Late Neolithic Scotland. It is the first study of these enigmatic artefacts since that undertaken by Dorothy Marshall in 1977 and includes all currently known examples in both museums and private hands, described and analysed in considerable detail.